Strategi Perencanaan dalam Peningkatan Kinerja Pendidik dan Tenaga Kependidikan di SMPN 40 Surabaya - Valentiara, Nadhea Kusuma; Fitri, Aghna Mar’atul (TSAQOFAH, 2024)
Management of Educators and Education Personnel is one of the characteristic indicators of the quality of a school. In the management of educators and education personnel there are also Planning Strategies for Improving the Performance of Educators and Education Personnel which have an influence on the potential for developing the performance of educators in schools. The aim of this research is to describe school principals' strategies for improving the quality of education starting from planning, implementation, to evaluation. The method used to obtain the results of this article is using qualitative methods, namely by conducting interviews and observations. The results of this research show that (1) what strategies are carried out by SMPN 40 Surabaya to be able to develop the performance of teaching and education staff, (2) to find out how to process teaching and education staff effectively, (3) to find out what the separate assessment criteria are for performance of SMPN 40 Surabaya teachers, (4) to find out how the principal's strategy is to work together with the committee to improve the quality of education.